2012
DOI: 10.1111/j.1744-9987.2012.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Study of the Efficacy and Safety of Sevelamer Hydrochloride and Lanthanum Carbonate in Japanese Patients Undergoing Hemodialysis

Abstract: Insufficient control of serum calcium and phosphate levels in patients undergoing hemodialysis is associated with increased mortality. As commonly used calcium-containing phosphate binders can cause arterial calcification, newly developed calcium-free phosphate binders, such as sevelamer hydrochloride (SH) and lanthanum carbonate (LC), have received much attention. We assessed the efficacy and safety of SH and LC treatment in Japanese patients undergoing hemodialysis in a prospective randomized open blinded en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…7 The average daily dose in the current review was significantly higher when compared to Kasai et al's review where the average daily dose was 945 mg for lanthanum and 2,971 mg for sevelamer hydrochloride. 11 This dose disparity correlated to decreased tablet burden in favor of lanthanum as seen in this study, which has been associated with a potentially positive influence on patient adherence. This study demonstrated a potential prescription cost savings for the medical center of approximately $4,500 monthly or $54,000 annually, if all study patients prescribed less than or equal to 9,600 mg of sevelamer carbonate per day were converted to lanthanum therapy.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…7 The average daily dose in the current review was significantly higher when compared to Kasai et al's review where the average daily dose was 945 mg for lanthanum and 2,971 mg for sevelamer hydrochloride. 11 This dose disparity correlated to decreased tablet burden in favor of lanthanum as seen in this study, which has been associated with a potentially positive influence on patient adherence. This study demonstrated a potential prescription cost savings for the medical center of approximately $4,500 monthly or $54,000 annually, if all study patients prescribed less than or equal to 9,600 mg of sevelamer carbonate per day were converted to lanthanum therapy.…”
Section: Discussionmentioning
confidence: 77%
“…5,10,11 Although lanthanum and sevelamer carbonate are only approved in ESRD patients, this evaluation along with previous literature support use in CKD stage 3-5 as well. 5,17 Both groups included a similar portion of patients who had active prescriptions for calcium acetate.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, arterial media calcification was observed in patients undergoing hemodialysis who consumed Ca-containing phosphate binders [6]. Randomized controlled trials on sevelamer and lanthanum in Japanese patients indicated identical levels of phosphate-binding efficacy [7]. Isakova et al also reported that treatment with phosphorus binders independently decreased mortality in patients [8].…”
Section: Discussionmentioning
confidence: 93%